Narasi Disparitas Higher-order Thinking Skill dan Scientific Thinking Skills Timur dan Barat dalam Sebuah Pengembangan Pemahaman yang Bertahan Lama - Sholihin, Anwar (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2020)
Al Quran is a book of arguments and books that challenge western and eastern thinkers to collide with the truth of correct thinking, for the defeat of concepts and methodologies, the west thinks harder to surpass it by denying the truth of the Quran. Sayangya timur (the Islamic community) tends to follow him to justify their post-truth. This paper aims to describe how the disparity narrative of Eastern (Islamic) and western Scientific thinking skills in the development of long-lasting understanding. This research is a qualitative literature study of how phenomenons are interpreted in the literature. Reflexive methods such as narrative inquiry, autoetnography, joint ethnography, and community dialogue methods. As a form of understanding, narrative inquiry helps us shape our understanding of complex events. From the results of the discussion, it can be concluded as follows: 1) Higher-order thinking skills and western scientific thinking skills tend to squeeze thoughts constantly towards the emptiness of the soul by accelerating the post-truth era. 2) Higher-order thinking skills and Eastern (Islamic) scientific thinking skills are integrated into three low, medium and high levels which analogize thinking in parallel 1 (horizontally or vertically) parallel 2 (horizontally and vertically) and systematically complex cyclically by staying on linguistic narrative and rejects the post-truth by itself.